Efektivitas Konseling Kelompok dalam Teknik Realita untuk Meningkatkan Kepercayaan Diri Mahasiswa Broken Home (Jurnal Wahana Konseling, 2025)
Broken homes can have a significant impact on children's psychological development, including in terms of self-confidence. The purpose of this study was to investigate the effectiveness of reality techniques in group counseling to increase the self-confidence of students from broken homes. The research method used was a quantitative approach with a quasi-experimental design, involving an experimental group that received group counseling intervention with reality techniques and a control group that did not receive intervention. The research participants were students who were identified as coming from broken homes and had low levels of self-confidence. Sampling was carried out using a purposive sampling technique (N = 5). The instrument used to measure self-confidence was a self-confidence scale, measured before and after the intervention. Data analysis used the Wilcoxon test to determine the difference in significant increases before and after treatment. The results showed that group counseling with reality techniques significantly increased the self-confidence of broken home students. The implications of the study indicate the importance of psychological support for broken home students to overcome self-confidence problems.